Characterizing Post-Storm Beach Recovery Modes: A Field-Based Morphodynamic Study from Dongdao Beach, China - Lulu Liu; Yan Sun; Run Liu; Daoheng Zhu; Zhaoguang Chen; Zhiqiang Li (Journal of Marine Science and Engineering)
The post-storm beach recovery process exhibits variability. Understanding its mechanisms is crucial for advancing the study of beach morphodynamics. This study involved a 25-day continuous field observation on Dongdao Beach, Hailing Island, Yangjiang City, Guangdong Province, following the passage of Typhoon Cempaka. The evolution of beach morphology and the spatiotemporal variations in erosion and accretion were analyzed to explore the key influencing factors, response mechanisms, and recovery modes during the short-term recovery process. The post-storm evolution of beach profile structures is predominantly influenced by major geomorphic units such as berms and sandbars, whereas localized responses are characterized by adjustments of fine-scale features like micro-troughs. The width of the supratidal zone and the position of the berm crest continuously fluctuate, while the slope of the intertidal zone increases or decreases as the berm crest migrates landward or seaward. The erosion–accretion process was complex and occurred in distinct stages, with marked spatial heterogeneity. In some areas, the beach experienced multiple short-term cycles of alternating erosion and accretion. Beach slope plays a significant role in short-term recovery. Three types of response relationships between beach unit-width volume and changes in slope were observed, with flatter beaches being more sensitive to changes in unit-width volume. Based on this, four recovery modes in the post-storm short-term recovery process were explored from the perspective of beach slope. This study provides theoretical support for managing beaches after storms and recommends the implementation of zoned and phased management strategies based on different recovery modes to enhance the efficiency and resilience of coastal recovery.